OAUNI non-detection of AT 2023pow in R band - Pereyra, Antonio (2023)
CCD imaging was performed of the NGC 1640 field using the OAUNI 51cm telescope at Huancayo Observatory, Peru, on 2023-08-19.310 (UT). No source is detected at the position of AT 2023pow (TNSTR-2023-1982) with limiting magnitude R ~ 18.5. This is consistent with the AT 2023pow report by T. Noguchi few hours after the detection alert. The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio133-2020 Fondecyt).